A influência de abolicionistas e escravocratas brasileiros na atuação de uma organização bancária no século XIX - Biscaia, Pedro (2018)
Organizational studies with historical bias seek the understanding of the phenomena through a perspective of historical-cultural contextualization of the object of study. This epistemological positioning breaks with presentism and universalism, typical of the functionalist analyzes. Thus, the production of knowledge about a given organization runs through the understanding of the construction of the specific historical and social context researched. From this approach, organizational studies on Brazilian companies are related to the understanding of the history, economy, social and political formation of the country. The history of Banco do Brasil is closely related to the history of Brazil. Since its first founding, there has been a great influence of the State and political groups in its administration. This work analyzed the influence of the slaveholders and abolitionists, during the nineteenth century, in Banco do Brasil business practices. The research was based on a bibliographical review of studies on the subject and research in newspapers of the time. After the right to exercise the function of issuing bank ceased, Banco do Brasil directed its action to agricultural mortgage financing. In these operations, enslaved persons were formally tied to contracts between the bank and its debtors. In cases of defaults, the bank executed the debts by auctioning the collateral. Much of the agricultural financing in this period was secured by the mortgage of slaves. The growth of the abolitionist movements and the emancipation of the slaves increased the defaults of contracts of this nature and, consequently, the bank suspended the agricultural financing until the definitive solution of the slavery question. The relationship between the interests of the bank, the state and the Brazilian slaveholder agrarian elite was presented during the course of the research. This context was fundamental to Banco do Brasil's practices understanding in the period and its specific management decisions. Issues related to slavery have generated social impact in the country to this day. Banco do Brasil was part of this history and currently adopts organizational practices focused on racial equity